O número de ouro, a sequência de Fibonacci e a contextualização de suas aplicações à aprendizagem em sala de aula para alunos do ensino fundamental II - NAZARÉ, Wenderson Araújo de (2022)
The focus of this work was to elaborate a bibliographic review on the golden number and the Fibonacci sequence with the objective of contributing as a base of study for students of elementary school II for the purpose of knowledge, learning and in the search to further integrate the concept of geometry, algebra, irrational numbers, proportions, arithmetic and ratio. Analyzing the subject on the subject, a qualitative research was obtained through academic google with about 15,000 researches related to the golden number and 2,470 on the Fibonacci sequence between the period 2011 - 2022 through which twenty one works were filtered for the construction of this work, two of which are directly related to teaching in schools, such as BNCC and PCN. In addition, the analysis was done in a descriptive way, allowing to significantly reduce the material that were cataloged as public collections, books, monographs, dissertations, course conclusion works, electronic journals, academic repositories and websites. To accomplish it, topics of the student's daily life were addressed so that they can visualize, identify and solve problems related to the subject in a critical and constructive way, improving their ability to reason and solve mathematics content, starting from their origin, followed by the its mathematical and geometric development to the realization of its applications in several areas of nature, as well as suggestions for activities based on this article. It is important to emphasize that this study is essential in the classroom, as it awakens the student's interest in the importance of mathematics in our daily lives. The results suggest that through this theme, figures, tables and graphs showed that the golden number is found in works of art such as the Mona lisa, in architecture as in the pyramid of Giza, in Biology as in the dimensions of the human body and even in the religion as in Christ's timetable. With this, it is concluded that the study of the golden number brings possibilities for the student to learn even more about Mathematics concepts, in addition to being interesting that makes what becomes motivating, making learning much more didactic and profitable.